Sınır Koşulları Ve Çözünürlüğün Sel Tahminindeki Etkileri: İstanbul Çalışması - Kömürcü, Müge (Fen Bilimleri Enstitüsü, 2015)
Sel olayları sonucunda önemli miktarlarda can kaybı ve ekonomik problemler oluşmaktadır. Bu çalışmada, sınır şartları ve çözünürlüğün Istanbul’daki sel tahminindeki etkisini aarştırmak amacı mezo ölçek model MM5 ile dört deney yapılmıştır. İlk deneyde, 18 km yatay çözünürlükte büyük bir bölge alınmıştır. İkinci deneyde, sınır koşulların etkisini incelemek amacı ile aynı çözünürlükte daha küçük bölge seçilmiştir. Bunun yanında, üçüncü bir deney ile ikinci deneyin alanına çözünürlüğün tahmindeki etkisine bakmak amacıyla 9km yatay çözünürlük uygulanmıştır. Son olarak son bir deney yapılarak, tüm deneylerden daha büyük bir 36 km çözünürlükte bir alan seçilmiş ve buna, 12 ve 4 km’lik yatay çözünürlükte iç alanlar eklenmiştir. Deney sonuçları NCEP Reanalysis alanları ile 850 ve 500mb da karşılaştırılmış ve tatmin edici sonuçlar alınmıştır. Günlük toplam yağış miktar ve alanları tüm deneyler için karşılaştırılmış ve düşük çözünürlükte daha detaylı sonuçlar alınmasına rağmen genel pattern tüm deneylerde benzer bulunmuştur.

Significant amounts of loss of lives and economical problems occur due to flooding events. Recently, it was observed that even without significant amounts of rainfall, flooding could be seen due to the impacts of urbanization. For this reason, it is essential to predict rainfall and flood. In this study, in order to analyze the effects of lateral boundaries and horizontal resolution on flood simulation in Istanbul, four experiments are done using mesoscale model MM5. In the first experiment, a large domain with 18 km horizontal resolution is selected. In the second experiment, a smaller domain with the same horizontal resolution was chosen, to see the impacts of lateral boundaries. Furthermore, a third experiment was employed with 9 km horizontal resolution on the same domain of the second experiment to see the impacts of the horizontal resolution. Finally, a last experiment was done, in order to observe the meteorological pattern better, and provide an accurate flow of information to the inner domains to be constructed, with a much larger domain than all the previous experiments, consisted of a coarse domain with horizontal resolution of 36 km, and inner two domains with horizontal resolutions of 12 and 4 km respectively. Results of experiments were verified with the NCEP Reanalysis fields of 500 and 850 mb and satisfactory results were obtained. Daily total accumulated rainfall amounts and locations were compared in each experiment, leading to the fact that although increased resolution yielded detailed results, overall precipitation pattern obtained was similar in all runs.
Effects Of Lateral Boundaries And Resolution On Flood Simulation: A Case Study For Istanbul
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2005
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2005
Keywords: yağış tahmini; MM5; sınır koşullar; çözünürlük; precipitation prediction; MM5; lateral boundaries; resolution